6-6x-3=-17+4x-10

Simple and best practice solution for 6-6x-3=-17+4x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-6x-3=-17+4x-10 equation:


Simplifying
6 + -6x + -3 = -17 + 4x + -10

Reorder the terms:
6 + -3 + -6x = -17 + 4x + -10

Combine like terms: 6 + -3 = 3
3 + -6x = -17 + 4x + -10

Reorder the terms:
3 + -6x = -17 + -10 + 4x

Combine like terms: -17 + -10 = -27
3 + -6x = -27 + 4x

Solving
3 + -6x = -27 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + -6x + -4x = -27 + 4x + -4x

Combine like terms: -6x + -4x = -10x
3 + -10x = -27 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + -10x = -27 + 0
3 + -10x = -27

Add '-3' to each side of the equation.
3 + -3 + -10x = -27 + -3

Combine like terms: 3 + -3 = 0
0 + -10x = -27 + -3
-10x = -27 + -3

Combine like terms: -27 + -3 = -30
-10x = -30

Divide each side by '-10'.
x = 3

Simplifying
x = 3

See similar equations:

| 7x+12=-5x-8 | | -2x-14=3x+11 | | 7x+12=-5-8 | | x^2-16+48=0 | | 1/5x+2=13 | | 3x+2.5=7 | | 2(x+4)=3(x+5) | | 2*4-2y=-4 | | 8x-3y+21=0 | | 15y=14(y+12) | | X/23=-39+3 | | 10x+3-9x=10 | | 2(6+a)= | | -5-7=-4+x | | x+3x=1200 | | 6(z-2)+5z-4= | | 5(q+7)= | | X-6x+8x-9x= | | 6q+2q= | | -(8y+2)-(-7y-6)=1 | | -(8y+2)-(-7-6)=1 | | 9y=8(y+1) | | 2[3-2(4-5)]= | | 396=3000(0.044)x | | 5/x+3/4=11/8 | | 9y-6=-3 | | (128x^13w^20)^1/5 | | X/43=-41+12 | | 4ln(x-1)=12 | | -8*8-2y=16 | | y-5/4=1-y/5 | | -8(-8)-2y=16 |

Equations solver categories